Pengaruh Dekanter Solid dan Plant Growth Promoting Rhizobacteria (PGPR) Terhadap Pertumbuhan dan Hasil Kedelai (Glycine max (L.) Merrill) - Buhaira Buhaira; Made Deviani Duaja; Sosiawan Nusifera (Universitas Batanghari, 2023)
Soybean (Glycine max (L) Merrill) is an important food crop because of its nutritional content, especially its high protein content. Increasing need is not balanced with increase in production. One of causal factors is low level of soil fertility. This research aimed to study the interaction effect of solid decanter dosage with PGPR concentration on the growth and yield of soybean plants. The experimentwas arranged in a randomized block design with factorial pattern consisted of 2 factors, namely solid decanter and PGPR. Solid decanter (K) comprisedtwo dose levels, namely: k1 = 10 ton.ha-1 solid decanter, and k2 = 15 ton.ha-1 solid decanter, while PGPR (P) comprised 3 concentration levels, namely: p0 = without PGPR (0%), p1 = PGPR 30%, p2 = PGPR 50%. Variables observed were plant height, number of branches, number of pods per plant, number of filled pods per plant, weight of seeds per plant, weight of 100 seeds and yield of plants. Data from the observations were statistically analyzed using analysis of variance (Anova). If the results of the analysis of variance showed significance, analysis was continued with mean comparison using LSD test at the α = 5% level. Results showed that there were interaction effect found on number of filled pods and the weight of 100 seeds. Meanwhile, there were no interaction effect foundonplant height, number of branches, number of pods per plant, seed weight per plant and yield. Thus, it was concluded that the provision of solid decanters of 10 ton.ha-1 to 15 ton.ha-1 and PGPR up to a concentration of 50% were not able to increase soybean crop yields.